2007
DOI: 10.1074/jbc.m701406200
|View full text |Cite
|
Sign up to set email alerts
|

SWI/SNF Activity Is Required for the Repression of Deoxyribonucleotide Triphosphate Metabolic Enzymes via the Recruitment of mSin3B

Abstract: The SWI/SNF chromatin remodeling complex plays a critical role in the coordination of gene expression with physiological stimuli. The synthetic enzymes ribonucleotide reductase, dihydrofolate reductase, and thymidylate synthase are coordinately regulated to ensure appropriate deoxyribonucleotide triphosphate levels. Particularly, these enzymes are actively repressed as cells exit the cell cycle through the action of E2F transcription factors and the retinoblastoma tumor suppressor/p107/p130 family of pocket pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…We observed over a 250% increase in both mild/moderate and severe dysplasia as compared to normal, indicating that this event is present in very early stage lesions. It has recently been reported that DHFR is subjected to RB mediated repression via SWI/SNF chromatin remodelling activity [ 29 ]. The increase in DHFR observed is in concordance with the expected downstream effects of decreased RB gene family repression.…”
Section: Discussionmentioning
confidence: 99%
“…We observed over a 250% increase in both mild/moderate and severe dysplasia as compared to normal, indicating that this event is present in very early stage lesions. It has recently been reported that DHFR is subjected to RB mediated repression via SWI/SNF chromatin remodelling activity [ 29 ]. The increase in DHFR observed is in concordance with the expected downstream effects of decreased RB gene family repression.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, more than 100 different proteins have been reported to associate with pRb-family proteins (Morris and Dyson 2001). Most of the proteins linked to pRb are chromatin-associated proteins with roles in transcriptional regulation, chromatin modification, and/or chromatin remodeling (Brehm et al 1998a; Ferreira et al 1998; Luo et al 1998; Magnaghi-Jaulin et al 1998a; Nielsen et al 2001a; Narita et al 2003; Gunawardena et al 2007; Litovchick et al 2007). …”
Section: The Prb Tumor Suppressormentioning
confidence: 99%
“…This role for SWI/SNF may be indirect, since it was later shown that SWI/SNF activates SRG1 (an intergenic transcript adjacent to SER3) which represses SER3 [25]. SWI/SNF is also required for repression of deoxyribonucleotide triphosphate metabolic enzymes during exit from the cell cycle [26]. Moreover, there are reports that link SWI/SNF to repression of the c-FOS proto-oncogene [27].…”
Section: Introductionmentioning
confidence: 99%